Multicultural identity integration and well-being: a qualitative exploration of variations in narrative coherence and multicultural identification - Yampolsky, Maya A.; Amiot, Catherine E.; de la Sablonnière, Roxane (Frontiers in Psychology, 2013)
Understanding the experiences of multicultural individuals is vital in our diverse populations. Multicultural people often need to navigate the different norms and values associated with their multiple cultural identities. Recent research on multicultural identification has focused on how individuals with multiple cultural groups manage these different identities within the self, and how this process predicts well-being. The current study built on this research by using a qualitative method to examine the process of configuring one’s identities within the self. The present study employed three of the four different multiple identity configurations in Amiot, de la Sablonnière, Terry & Smith’s (2007) cognitive-developmental model of social identity integration: categorization, where people identify with one of their cultural groups over others; compartmentalization, where individuals maintain multiple, separate identities within themselves; and integration, where people link their multiple cultural identities. Life narratives were used to investigate the relationship between each of these configurations and well-being, as indicated by narrative coherence. It was expected that individuals with integrated cultural identities would report greater narrative coherence than individuals who compartmentalized and categorized their cultural identities. For all twenty-two participants, identity integration was significantly and positively related to narrative coherence, while compartmentalization was significantly and negatively related to narrative coherence. ANOVAs revealed that integrated and categorized participants reported significantly greater narrative coherence than compartmentalized participants. These findings are discussed in light of previous research on multicultural identity integration.